Perempuan dan Pendidikan: Refleksi atas Pendidikan Berperspektif Gender - Ana Rosilawati (PSGA LP2M IAIN Pontianak, 2014)
Education is a significant aspect which uses gender paradigm as a analytical tool to portray the women existence, especially in the equality and the equity values. Furthermore, the using of gender paradigm in an education world concerns on the equal opportunity given among men and women. This effort begins with the constructive process on differential behavior to women. Moreover, the weakness of women is identically considered as a ‘kodrat’. Therefore, the writing is a critical reflection to the reality life of women in education world.